Making Art at Home During the COVID-19 Pandemic: Instagram, Young Visitors, and Museum Collections - Huebner, Emma June (Canadian Review of Art Education / Revue canadienne d'éducation artistique)

(untitled) (Canadian Society for Education through Art, 2022)
This paper examines some of the ways that Canadian art museum education departments used Instagram during the COVID-19 pandemic, particularly for young virtual visitors. The author studied this use of Instagram through a visual content analysis of ten Canadian museums’ educational posts, stories and IGTV videos, using the theory of connectivism and the way learners can engage with learning opportunities outside of their physical environments. The findings from this study reveal that Instagram became instrumental in allowing museum educators to continue their mission of promoting meaningful engagement with collections for their visitors.